The Effect of Callus Age on Biomass and Flavonoid Production in Talinum paniculatum In Vitro Culture - Restiani, Ratih; Aditiyarini, Dwi; Dolonseda, Anggel Christia; Nathania, Yohana Elsa (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Talinum paniculatum (Javanese Ginseng) is an herbaceous plant belonging to Talinaceae family that has been known as an important medicinal plant. Flavonoid is one of the prominent bioactive compounds that are contained in all parts of T. paniculatum and has been known for its several bioactivities, including antioxidant, anti-inflammatory, antimicrobial, antidiabetic, and anti-cancer. Callus culture can be used to ensure the quantity and quality of flavonoid production. Callus age is one of the important factors that needs to be considered in order to produce optimum biomass and flavonoid production. Therefore, this research aimed to investigate the effect of callus age on biomass and flavonoid production in T. panicultaum in vitro culture. Young leaves were used as an explant, and callus induction was performed using MS solid media supplemented with kinetin 3 mg/L and 2.4-D 2 mg/L. Biomass and flavonoid production were observed during 0, 28, 35, 42, and 49 days. Results showed that biomass and flavonoid production were influenced by callus age. The production of flavonoid in T. paniculatum callus culture was not linear with the growth of callus (biomass), and the optimum flavonoid production resulted in the 28th days of callus age (49.100 mg QE/g), while the optimum biomass resulted in the 49th days of callus age (4.295 g). It can be concluded that the optimum conditions for biomass and flavonoid production in T. paniculatum callus culture are influenced by different callus ages